Figs, Farmers, and Futures : A Case Study on Purandar Highlands’ Expansion Dilemma - Joshi, Sumita P.; Saha, Shantanu; Pendse, Meenal; Ursal, Rohan Satish (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined the strategic growth dilemma faced by the Purandar Highlands Farmer Producer Company (FPC), a farmer-led agri-enterprise producing GI-tagged figs and value-added products. The case explored whether the company should deepen its domestic presence or scale internationally to achieve long-term sustainability. Design/Methodology/Approach : The study followed a qualitative single-case approach based on a semi-structured interview with the company’s founder, supplemented by secondary data from company records, media articles, and policy reports. Strategic tools such as SWOT analysis and Ansoff’s Matrix were applied to interpret the firm’s growth pathways. Findings : The findings indicated that PH-FPC faced distinct opportunities and risks in domestic and international markets. While the Indian market offered logistical ease and stronger farmer integration, global expansion provided higher margins and branding potential but required regulatory readiness and capital investment. A phased hybrid expansion strategy emerged as the most appropriate solution. Practical Implications : The case offered actionable insights for farmer-led organizations, policymakers, and agri-FMCG entrepreneurs on scaling GI-tagged produce. It also contributed to understanding operational bottlenecks and branding challenges in the rural-to-retail value chain. Originality/Value : The study added to the limited literature on rural entrepreneurship and FPO-based growth strategies in the Indian agri-FMCG sector. It uniquely connected farmer collectives, GI-based branding, and strategic management decisions.